GOOD GOVERNANCE (TATA KELOLA PEMERINTAHAN YANG BAIK) DALAM PEMBERIAN IZIN OLEH PEMERINTAH DAERAH DI BIDANG PERTAMBANGAN - Oheo K Haris (Universitas Airlangga, 2015)
Instruments in terms of the provisions of the mining law has been regulated by law No. 11 of 1967, in which the government's legal position is not comparable to the investors. granting it is the government or ruling authority in order to protect the interests of citizens in order to establish a concrete action even if it deviates from the provisions that are prohibited. Good governance or good governance is closely related to human rights. Thus, that one of the bases existence of a support or foundation of a discretion in this case the nature of the license by the government especially the mining sector is the presence of good governance or Good pemeritahan Governancne so as to create a harmonization as state officials